Performance of Non-rotating Shoulder Tool in Weld Joint and Forces of Friction Stir Welding - Moch. Syamsul Ma'arif; Christopher David Cook (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2019)
Lighter construction in the structure of transportation make industries rely on aluminium as construction materials and new technology of joining such as friction stir welding become increasingly applied. Since welding force in the process is considered high so that many researches are focussed on this area. In this research, a new method of welding by using non-rotating shoulder tool and combined with pre heating was investigated. The result give confirmation that the methods was proven to be adequate to produce sound welding when the parameters chosen was rightly. Eventhough the method was able to lower the force but significant results only observed for Fx while another force, i.e. Fz, did not have similar significant results. Non-rotating shoulder with additional heat input has limited capability in lowering forces in Fz because of its design, while has very good capability to lower Fx. Also, it was obvious that the heat source using propane torch was not adequate to give uniform additional heat input in all welding phase and still need another moee porent heat source in order to improve the performance.